Peak apical recoil rate is a simplified index of left ventricular untwist: validation and application for assessment of diastolic function in children - Yubbu, Putri; Kauffman, Hunter; Calderon-Anyosa, Renzo; Montero, Andrea E.; Sato, Tomoyuki; Matsubara, Daisuke; Banerjee, Anirban (Springer, 2022)
The use of untwisting rate as a novel index of LV diastolic function in clinical practice has been limited due to its tedious and time-consuming analysis. Therefore, we simplify the untwist measurement by only measuring the LV apex's recoil rate and validating and applying peak apical recoil rate (PARR) as an index of diastolic dysfunction (DD) in pediatric subjects during increased and decreased lusitropic states. We recruited 153 healthy subjects (mean age 13.8 ± 2.9 years), of whom 48 performed straight leg raising exercise and an additional 46 patients (mean 8.4 ± 5.6 years) with documented pulmonary capillary wedge pressures (PCWP) (validation cohort). In addition, we studied 16 dilated cardiomyopathy patients (mean age 9.5 ± 6.3 years) (application cohort). PARR and isovolumic relaxation time (IVRT) were compared to PCWP. Both PARR and PARR normalized by heart rate (nPARR) were excellent in detecting patients with PCWP ≥ 12 mmHg and greatly superior to IVRT in this respect (AUC: 0.98, 95% CI [0.96, 1.0] vs. AUC: 0.7 95%CI [0.54,0.86]). In DCM patients, PARR and nPARR were greatly decreased compared to controls (− 38.6 ± 18.6º/s vs − 63.1 ± 16.3º /s, p < 0.001) and (− 0.43 ± 0.20 º/ s/min vs − 0.83 ± 0.28º/s/min, p < 0.0001) but increased with straight leg raising exercise (− 59.4 ± 19.4º/s vs − 97.8 ± 39.0 º/s, p < 0.01) and − 0.85 ± 0.36 vs − 1.4 ± 0.62 º/s/min (p < 0.0001) respectively. PARR and nPARR successfully detected increased and decreased lusitropic states and superior to IVRT in correlation with PCWP. This highly reproducible parameter offers incremental value over traditional indices of DD and may potentially serve as a useful index of elevated PCWP in children.